Maintenance treatment after induction therapy in non-small cell lung cancer: latest evidence and clinical implications. (January 2014) - Gentzler, Ryan D.; Patel, Jyoti D.
Non-small cell lung cancer (NSCLC) is the leading cause of cancer death in the industrialized world. Despite significant progress in early stage disease, survival rates for advanced disease remain low. Maintenance therapy is a treatment strategy that has been investigated extensively in NSCLC. Therapies that have been studied in this setting in randomized trials to date include chemotherapy and molecularly targeted agents. Following the development of multiple new agents that show activity in NSCLC and have a tolerable side-effect profile, there has been increasing interest in utilizing them to maintain response to initial therapy after treatment with platinum-based doublets. Two effective strategies have evolved: continuation and switch maintenance. Despite improvements in progression-free survival and often overall survival on multiple clinical trials, there remains considerable controversy around this treatment paradigm. Here, we briefly outline the evolution of this treatment strategy and examine the available data, including recently updated data from the PARAMOUNT, AVAPERL, and PointBreak maintenance trials. Ultimately, the decision to use maintenance chemotherapy requires a nuanced discussion between the patient and physician that adequately assesses benefits of prolonged therapy and impact in terms of toxicity, quality of life, and financial cost.